Concentration quenching and thermal activation of the luminescence from terbium‐doped a ‐SiC:H and c ‐AlN thin films. Issue 1 (29th November 2012) - Guerra, J. Andres; Benz, Felix; Zanatta, A. Ricardo; Strunk, Horst P.; Winnacker, Albrecht; Weingärtner, Roland
Abstract The effect of terbium (Tb) doping on the photoluminescence (PL) of crystalline aluminum nitride (c ‐AlN) and amorphous hydrogenated silicon carbide (a ‐SiC:H) thin films has been investigated for different Tb atomic concentrations. The samples were prepared by DC and RF magnetron reactive sputtering techniques covering the concentration range of Tb from 0.5 to 11 at.%. The Tb‐related light emission versus the Tb concentration is reported for annealing temperatures of 450 °C, 750 °C and 1000 °C. In the low concentration region the intensity exhibits a linear increase and its slope is enhanced with the annealing temperature giving an activation energy of 0.106 eV in an Arrhenius plot. In the high concentration region an exponential decay is recorded which is almost independent on the host material, its structure and the annealing process (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)